Single cell transcriptomics identifies distinct choroid cell populations involved in visually guided eye growth - Summers, Jody A.; Jones, Kenneth L. (Frontiers in Ophthalmology, 2023)
Postnatal ocular growth is regulated by a vision-dependent mechanism, termed emmetropization, which acts to minimize refractive error through coordinated growth of the ocular tissues. Many studies suggest that Tthe ocular choroid participates in the emmetropization process via the production of scleral growth regulators that control ocular elongation and refractionve development.To elucidate the role of the choroid in emmetropization, we used single-cell RNA sequencing (scRNA-seq) to characterize the cell populations in the chick choroid and compare gene expression changes in these cell populations when the during conditions in which the eye is undergoing emmetropization. Emmetropization was modeled by inducing form deprivation myopia in 3 -4 day old chicks via application of translucent occluders to one eye for a period of 10 days followed by 24 hrs of unrestricted vision (by removing the occluder). Numerous studies have previously shown that visual form deprivation stimulates axial elongation and myopia, and upon removal of the occluder, the myopic chick eye rapidly slows its rate of axial elongation to recover from the induced myopia and regain emmetropia. The contralateral, untreated eyes served as controls. UMAP clustering analysis identified 24 distinct cell clusters in all chick choroids. 7 clusters were identified as fibroblast subpopulations; 5 clusters represented different populations of endothelial cells; 4 clusters were CD45+ macrophages, T cells and B cells; 3 clusters were Schwann cell subpopulations; and 2 clusters were identified as melanocytes. Additionally, single populations of RBCs, plasma cells and neuronal cells were identified. Significant changes in gene expression between control and treated choroids were identified in 17 cell clusters, representing 95% of total choroidal cells. The majority of significant gene expression changes were relatively small (< 2 fold). The greatesthighest changes in gene expression were identified in a rare cell population (0.11% -0.49% of total choroidal cells). This cell population expressed high levels of neuron-specific genes as well as several opsin genes suggestive of a rare neuronal cell population that is potentially light sensitive. Our results, for the first time, provide a comprehensive profile of the major choroidal cell types and their gene expression changes during the process of emmetropization and